2019
DOI: 10.1021/acs.energyfuels.9b02346
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carbon Dioxide on Laminar Burning Speed and Flame Instability of Methane/Air and Propane/Air Mixtures: A Literature Review

Abstract: This work reviews the impact of carbon dioxide (CO 2 ) on laminar burning speed and stability of the flame for methane (CH 4 ) and propane (C 3 H 8 ) combustion with air. Mixtures of CH 4 and CO 2 , also known as biogas, are considered as low-cost alternative fuels. Biogas is widely used in various industrial and residential applications. Mixtures of C 3 H 8 and CO 2 are considered as alternative refrigerants with low global warming potential and low flammability. Laminar burning speeds were reported using dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…The environmental benefit by producing energy from biogas is deeply appreciated through the reduction of gas emissions that exhibit a greenhouse effect by preventing its release into the atmosphere. Even if the biogas has a low heating value (about 3000-6000 kcal/m 3 ) compared to natural gas (about 8000-9000 kcal/m 3 ) or liquefied petroleum gas (about 25,000-28,000 kcal/m 3 ), its total chemical energy is sufficient to serve as a basis for the production of the heat and electricity that can be further used for domestic heating and cooking, or to feed internal combustion engines, gas turbines, fuel cells, or cogeneration systems [1][2][3][4][5]. A schematic diagram for biogas production and its applications is given in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The environmental benefit by producing energy from biogas is deeply appreciated through the reduction of gas emissions that exhibit a greenhouse effect by preventing its release into the atmosphere. Even if the biogas has a low heating value (about 3000-6000 kcal/m 3 ) compared to natural gas (about 8000-9000 kcal/m 3 ) or liquefied petroleum gas (about 25,000-28,000 kcal/m 3 ), its total chemical energy is sufficient to serve as a basis for the production of the heat and electricity that can be further used for domestic heating and cooking, or to feed internal combustion engines, gas turbines, fuel cells, or cogeneration systems [1][2][3][4][5]. A schematic diagram for biogas production and its applications is given in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…A schematic diagram for biogas production and its applications is given in Figure 1. and cooking, or to feed internal combustion engines, gas turbines, fuel cells, or cogeneration systems [1][2][3][4][5]. A schematic diagram for biogas production and its applications is given in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the effects of high fuel loading and the associated ignition behavior with immense CO2 dilution have not been investigated in detail. Studies of oxy-methane combustion with CO2 dilution have been performed in previous literature [10][11][12][13][14][15][16][17], though largely at intermediate to lower pressures [14,18,19] in a shock tube. For example, Hargis et al has investigated oxy-fuel combustion within a high pressure shock tube at pressures from 1 to 10 atm and 1450 to 1900 K; it was observed that increasing the level of CO2led to increased bifurcation.…”
Section: Introductionmentioning
confidence: 99%